An optimisation study of the modified deep-hole drilling technique using finite element analyses applied to a stainless steel ring welded circular disc. (July 2017) - Zheng, Gang; Hossain, Sayeed; Kingston, Ed; Truman, Christopher E.; Smith, David J.
Highlights: A complex residual stress field is generated by the partial welding of an austenitic stainless steel circular disc. Neutron diffraction measurement validates the numerical model. Finite element simulation of the deep-hole drilling technique is used to highlight the influence of plasticity. Extensive FEA simulation is used to demonstrate how (a) to account for plasticity and (b) to avoid plasticity in deep-hole drilling method. Abstract: A circular disc containing a partial ring weld was devised to create high levels of residual stress in a relatively small specimen. The aim of the study was to utilise the complex residual stress generated within the weld and to extend the recently developed novel application of the deep-hole drilling technique in measuring residual stresses well over yield stress. This paper presents (1) finite element analysis (FEA) simulation of the residual stresses due to partial welding in an austenitic stainless steel circular disc, (2) measurement of residual stress using non-destructive and semi-destructive techniques and (3) simulation of the semi-destructive residual stress measurement technique. Comparison is made between the FEA predicted residual stress in the weld, the measurements and the reconstructed residual stresses of the measurements. The purpose of the residual stress measurement was to validate the FEA predicted weld residual stress in the circular disc. The FEA simulation of the measurement method was used (1) to explain any discrepancy between the measured and FEA predicted stresses and (2) to further modify and extend the present deep-hole drilling technique and improve its accuracy. The close correlations confirmed the suitability of new modifications made in the deep-hole drilling technique to account for plasticity when measuring near yield residual stresses present in a component. Graphical abstract: